Får man bygga hur som helst? En analys av anpassningskravet i plan- och bygglagen - von Friesendorff,Johan (2025)
When granting a building permit for changes in detailed development areas, such as alterations and new construction, several requirements must be met. The application must comply with the detailed development plan, but also that the applicable regulations regarding the requirements and protective provisions are complied with. One of these requirements is the adaptation requirement (anpassningskravet) in Chapter 2, Section 6, item 1 of the Planning and Building Act (Plan- och bygglag (2010:900)). This thesis aims, through a doctrinal legal method, to examine preparatory works, legislative text and legal commentaries in order to clarify the applicable law. The thesis also analyses a comprehensive survey of case law, both recent decisions and older ones. The purpose of this is to investigate how the courts interpret the adaptation requirement, but also the related provisions regarding the assessment of building permit applications. The courts in the cases mentioned above develop their interpretation of the adaptation requirement and gives a synthesis on how it should be implemented in the issue at hand. The contemporary legal cases clarify that the adaptation requirement can constitute an independent basis for assessment but is seldom enough to revoke a building permit. Other factors, such as a negative impact on the surroundings, breach of provisions or failure to comply with current detailed development plan, becomes practically mandatory requirements. The analysis and summary show that it is hard to give an extensive statement on the field. What can be said, regarding the legal cases, is that there is a tendency from the highest instance, often the Land and Environment Court of Appeal (Mark- och miljööverdomstolen), to interpret the adaptation requirement quite liberally. Less restrictively than the preparatory works and legal commentaries imply. In my view, this presents a problem, as it results in reduced predictability in practical application. The conclusion is therefore that the legal review of the adaptation requirement is neglected to too great an extent and that a revision of the legislative text at hand is necessary. This is illustrated not least in MÖD 2015:26.
Keywords: Fastighetsrätt; förvaltningsrätt; plan- och bygglagen; PBL; ÄPBL; bygglov; detaljplan; anpassningskravet; byggnadsverks utformning; varsamhetskravet; förvanskningsförbudet